Attitude as mediating variable on relationship among participation, awareness and perception on bebas plastik campaign - Tan, Jian Shiang; Wok, Saodah (University College of Islam Melaka, 2017)
It has been several years since some states in Malaysia had banned plastic bags for a day. The Selangor state government had launched BebasPlastik Campaign on 1st January 2017 where it bans plastic bags seven days a week. As such, the objectives of this research are (1) to analyze the relationship among awareness, perception, attitude and participation in BebasPlastik Campaign and (2) to determine the mediating effect of attitude on relationship among awareness, perception and participation in BebasPlastik Campaign. The Social Learning Theory (Bandura, 1971) is used to explain the effects of awareness, perception, attitude and participation in BebasPlastik Campaign. A total of 430 Malaysian university students were identified in this study; which employs the quantitative research design using a self-administrated survey questionnaire as its research instrument. Results show that there is a positive relationship among all variables. Furthermore, attitude fully mediates the relationship between perception and participation. In addition, attitude only partially mediates the relationship between awareness and participation. Students may not know much about the BebasPlastik Campaign but their participation in BebasPlastik Campaign is high.